Integration of SDGs in Pesantren: Building Ecological Awareness among Santri - Fitriani, Namiyah; Zaki, Muhammad; Kabalmay, Taqiyuddin; Huda, Miftahul; Hidayatullah , M Baihaki (International Journal of Research and Community Empowerment, 2025)
Islamic boarding schools (Pesantren) in Indonesia have begun integrating the principles of the Sustainable Development Goals (SDGs) into their educational systems to promote ecological awareness and sustainable living among students (Santri). The aim is to explore the integration of the Sustainable Development Goals (SDGs) in the education and environmental framework at one of Pesantren in Lombok, with a focus on developing ecological awareness among Santri. This research highlights the important role of quality education, particularly in Pesantren, in addressing contemporary environmental challenges. Using a qualitative research approach with a case study methodology, data was collected through interviews with alumni and a literature review. The results showed that Islamic boarding schools have successfully implemented various programs, such as environmentally friendly policies, Islamic-based environmental curriculum, and extracurricular activities centered on nature contemplation. These initiatives not only promote environmental stewardship, but also empower students to actively participate in sustainability efforts. This study concludes that the integration of SDGs in Pesantren education practices significantly contributes to building ecological awareness and is aligned with the broader goals of sustainable development. This research makes a real contribution to the development of sustainable education and environmental conservation practices in Pesantren. The results of this study are not only academically relevant, but can also serve as a concrete example for other Pesantren that want to implement the principles of the SDGs.